Manfaat visual keberadaan hutan kota Padang Golf Halim - Syahadat, Ray March; Putra, Priambudi Trie (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020, 2020)
Golf course landscape is a form of green open space. Besides comprising a game area, the golf course landscape also has a buffer area that can be categorized as an urban forest. Halim Golf Course is one of the golf courses in Jakarta which has a non-game area in the form of urban forest. Studies on the value of the visual benefits of golf courses are rarely conducted. This study aims to determine the visual benefits of urban forest of Halim Golf Course. The method used is the assessment of visual quality with the SBE method and impression evaluation with the semantic differential method. The results obtained show that urban forests in the form of golf courses generally have aesthetic value. In addition, urban forests that are neatly arranged and not too dense are preferred.